Techniques for measuring indoor radicals and radical precursors. Issue 7 (9th August 2022) - Alvarez, Elena Gómez; Carslaw, Nicola; Dusanter, Sébastien; Edwards, Pete; Gábor Mihucz, Viktor; Heard, Dwayne; Kleffmann, Jörg; Nehr, Sascha; Schoemacker, Coralie; Venables, Dean
Abstract: Radicals and their precursors play a central role in the chemical transformations occurring in indoor air and on indoor surfaces. Such species include OH, HO2, peroxy radicals, nitrous acid, reactive chlorine species, NO3, N2 O5, Criegee intermediates, and glyoxal and methylglyoxal. Recent advances on instrumental analysis and modeling studies have demonstrated the need for a wider range of measurements of radical species and their precursors in indoor air. This work reviews measurement techniques and provides considerations for indoor measurements of several radicals and their precursors. Techniques to determine the actinic flux are also presented owing to the relevance of photolytically-initiated processes indoors. This review is also intended to provide pointers for those wanting to learn more about measurements of radicals indoors.